TOTAL FENOLIK,FLAVONOID SERTA AKTIVITAS ANTIOKSIDAN EKSTRAK n-HEKSANA, DIKLOROMETAN DAN METANOL Amaranthus spinosus L EM5-BAWANG PUTIH - Yondra Arif D; Christine Christine Jose; Hilwan Yuda Teruna (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The objective of this study was to analyze the total phenolics, total flavonoids, and antioxidant activities of Amaranthus spinosus L leaves. During cultivation, these plants were treated with 2 treatments, biocontrol Effective Microorganism 5 (EM5) garlic and control (water). The A. spinosus L leaves were dried using freeze dryer and extracted by dissolving n-hexane, dicloromethane (DCM) and methanol. The results showed that A.spinosus L leaves treated with biocontrol had the highest total phenolic, total flavonoid and antioxidant activity content compare to the control. The total phenolic, total flavonoid, 2,2 diphenyl-1-picrylhydrazyl (DPPH) and Nitric Oxide (NO) radical scavenging were the highest on DCM extract with each value of 74,656 mg Gallic Acid Equivalent (GAE)/g of dry weight (DW), 22,337 mg Catechin Equivalent (CE)/g DW, 0,373 mg/mL and 0,025 mg/mL. n-Hexane extract had the highest antioxidant activity on Ferric Thiocyanate (FTC) test (27,615 %), meanwhile methanol extract indicated the highest antioxidant activity on FRAP test (1,022 mmol Fe+2/g DW). From this study, it can be concluded that A. spinosus L leaves with biocontrol Effective Microorganism 5 (EM5) garlic can increase the phenolic, flavonoids and antioxidant activitiy contents of A. spinosus L plant.